"In transition: ensuring the sexual and reproductive health and rights of transgender populations." A roundtable discussion. Issue 52 (1st January 2018) - Gruskin, Sofia; Everhart, Avery; Olivia, Diana Feliz; Baral, Stefan; Reisner, Sari L; Kismödi, Eszter; Cruz, David; Klemmer, Cary; Reich, Michael R; Ferguson, Laura
Abstract: This roundtable discussion is the result of a research symposium entitled In Transition: Gender [Identity], Law & Global Health where participants took up the challenge to engage with the question: What will it take to ensure the sexual and reproductive health and rights (SRHR) of transgender populations across the globe? The barriers to overcome are fierce, and include not only lack of access to health services and insurance but also stigma and discrimination, harassment, violence, and violations of rights at every turn. Transgender people must of course lead any sort of initiatives to improve their lives, even as partnerships are needed to build capacity, translate lived experience into usable data, and to make strategic decisions. The SRHR of transgender people can only be addressed with attention to the social, cultural, legal, historical, and political contexts in which people are situated, with social, psychological, medical, and legal gender affirmation as a key priority shaping any intervention. Bringing together nine diverse yet complementary perspectives, our intent is to jumpstart a global and multigenerational conversation among transgender activists, lawyers, policy-makers, programmers, epidemiologists, economists, social workers, clinicians and all other stakeholders to help think through priority areas of focus that will support the needs, rights, and health of transgender populations. Making the changes envisioned here is possible but it will require not only the advocacy, policy, programmatic and research directions presented here but also struggle and action locally, nationally, and globally.